Analisis Pengaruh Media Sosial Pada Masa Pandemi Covid-19 Terhadap Pembelajaran Mahasiswa Menggunakan Metode Fuzzy Logic - Lucky Lhaura Van FC; Fajrizal Fajrizal; Yuvi Darmayunata (Jurnal Inovtek Polbeng Seri Informatika, 2021)
Abstrack– The effect of social media use has been dramatically increased during the Covid-19 pandemic in the earlier of 2020. Meanwhile, there are conflicting findings among the scholars regarding the significance of the effects, leading to an unclear conclusion for the impact on students' learning process. The use of social media by the students of the Faculty of Computer Science in Universitas Lancang Kuning runs linearly with the learning process within the courses. This phenomenon encourages students to use WhatsApp, Facebook, YouTube, Instagram, and other platforms, proving the strength of the internet in students' lives. This study used Fuzzy Logic to analyze social media's effect on students' learning process in the Faculty of Computer Science of Universitas Lancang Kuning. By employing 91 students, the result reveals that the social media was in the 60 (of 51-70 ran).Keywords – Social Media,college student,Fuzzy Logic